Development of defects free stainless steel parts using powder injection molding - Muhammad Rafi Raza, Faiz Ahmad, M.A Omar, Ali S. Muhsan, (2017)
Austenitic 816L Stainless Steel (SS) is widely used in aerospace, automotive, sports and medical industries due to its mechanical properties and corrosion resistance. Defects free molding of parts depends upon the features of feedstock. In powder injection molding, feedstock preparation is critical step and any deficiency at this stage cannot be retrieve in latter steps. The objective of this research work is to optimize solid loading for defects free injection molded parts